2002
DOI: 10.1128/jcm.40.11.4230-4234.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Causative Organism of Tuberculous Lymphadenitis in Ethiopia by PCR

Abstract: Tuberculous lymphadenitis (TBLN) is a common form of extrapulmonary tuberculosis with multiple differential diagnoses. Demonstration of the etiologic agent by smear microscopy or culture of fine needle aspirate (FNA) specimens is often unsuccessful. FNA specimens from 40 patients presenting at a rural health center in South Ethiopia and diagnosed as positive for TBLN on the basis of clinical and cytological criteria were analyzed for mycobacterial DNA by PCR. Thirty (75%) had cervical lymphadenitis and 11 (27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 24 publications
7
93
0
1
Order By: Relevance
“…The positivity rate varies from 61 to 94 % but it is found to be the most sensitive technique (Kim et al, 1996;Ersoz et al, 1998;Manitchotpisit et al, 1999;Baek et al, 2000;Goel et al, 2001;Kidane et al, 2002). The PCR positivities in cases of granuloma only and granuloma with necrosis are reported to be 42 % each, and 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The positivity rate varies from 61 to 94 % but it is found to be the most sensitive technique (Kim et al, 1996;Ersoz et al, 1998;Manitchotpisit et al, 1999;Baek et al, 2000;Goel et al, 2001;Kidane et al, 2002). The PCR positivities in cases of granuloma only and granuloma with necrosis are reported to be 42 % each, and 15 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to this, Kiros (1998) Furthermore, the author indicated that a higher prevalence of BTB in cattle owned by tuberculous patients was found than in cattle owned by nontuberculous owners, which suggests the significant role of M. bovis in the incidences of tuberculosis in humans (Regassa, 2005). In addition, Kidane et al (2002) indicated that M. bovis along with other MTC species were found to be a cause for tuberculous lymphadenitis in humans.…”
Section: Undertaken Studies In the Human Populationsmentioning
confidence: 99%
“…BTB in the human population mainly takes place through drinking raw milk and occur in the extra-pulmonary form in the cervical lymphadenitis form in particular. Recently, Kidane et al (2002) indicated that M. bovis was found to be a cause for tuberculous lymphadenitis in 17.1% of 29 human tuberculosis cases in Ethiopia. The proportion of which BTB contributes to the total of tuberculosis cases in humans depends on the prevalence of the disease in cattle, socioeconomic conditions, consumer habits, practiced food hygiene and medical prophylaxis measures.…”
Section: Zoonotic Importance Of Bovine Tuberculosis In Ethiopiamentioning
confidence: 99%
“…Among members of the Mycobacterium tuberculosis complex (MTC), M. tuberculosis and M. bovis have been implicated as the most common causes of tuberculous lymphadenitis (TBLN) [3,4,5,6]. In Ethiopia, little has been done to identify how M. bovis causes human TB, despite the population's routine consumption of unpasteurized milk and raw meat.…”
Section: Introductionmentioning
confidence: 99%